МОДИФИКАЦИЯ ГИДРОЛИЗНОГО ЛИГНИНА РАСТВОРАМИ ПЕРМАНГАНАТА КАЛИЯ - Далимова , Гуландом (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The work shows that as a result of permanganate oxidation, modification of the structure and properties of hydrolytic lignin occurs, which was revealed by a comparative study of the IR spectral and sorption characteristics of the original and modified lignin derivatives.